A Study on the Decision-Making of Students Enrolling at Luang Prabang Technical-Vocational College; Academic year 2025-2026 - CHANTHASITH, Latikone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research investigated the decision-making of students enrolling at Luang Prabang Technical-Vocational College. The data collection conducted in quantitative research approach with a questionnaire. The sample including 243 students currently studying at the college in the academic year 2025-2026. The data were analyzed by SPSS version 21. Using descriptive statistics including mean ( ) and standard deviation (SD). The variables encompassed 4 aspects: (1) motivation to study, (2) institutional image and credibility, (3) personal capability, and (4) socio-economic factors. The results revealed that the overall level of students’ decision-making at Luang Prabang Technical-Vocational College was high ( = 4.12, SD = 0.58). Considering to micro aspects, the results show that the motivation to study showed the highest mean score ( = 4.35, SD =0,65), followed by the institutional image and credibility ( = 4.18, SD =0,60), whereas the personal capability and socio-economic factors were at a moderate level. These findings prove that making a positive image and effectively advertising curriculum information are crucial factors in attracting students. So, the institution should focus on public relations activities, curriculum promotion, and the development of learning environment. These activities will enhance students' motivation to enroll. The findings also provide valuable fundamental information for the institution's policy brief and planning for sustainable student recruitment.